Experimental assessment of diazotroph responses to elevated seawater pCO₂ in the North Pacific Subtropical Gyre - Böttjer, Daniela; Karl, David M.; Letelier, Ricardo M.; Viviani, Donn A.; Church, Matthew J.
We examined short-term (24–72 h) responses of naturally occurringmarine N2 fixing microorganisms (termed diazotrophs) to abrupt increases in the partial pressure of carbon dioxide (pCO2) in seawater during nine incubation experiments conducted between May 2010 and September 2012 at Station ALOHA (A Long-term Oligotrophic Habitat Assessment) (22°45′N, 158°W) in the North Pacific Subtropical Gyre (NPSG). Rates of N2 fixation, nitrogenase (nifH) gene abundances and transcripts of six major groups of cyanobacterial diazotrophs (including both unicellular and filamentous phylotypes), and rates of primary productivity (as measured by 14C-bicarbonate assimilation into plankton biomass) were determined under contemporary (~390 ppm) and elevated pCO2 conditions (~1100 ppm). Quantitative polymerase chain reaction (QPCR) amplification of planktonic nifH genes revealed that unicellular cyanobacteria phylotypes dominated gene abundances during these experiments. In the majority of experiments (seven out of nine), elevated pCO2 did not significantly influence rates of dinitrogen (N2) fixation or primary productivity (two-way analysis of variance (ANOVA), P>0.05). During two experiments, rates of N2 fixation and primary productivity were significantly lower (by 79 to 82% and 52 to 72%, respectively) in the elevated pCO2 treatments relative to the ambient controls (two-way ANOVA, P<0.05). QPCR amplification of nifH genes and gene transcripts revealed that diazotroph abundances and nifH gene expression were largely unchanged by the perturbation of the seawater pCO2. Our results suggest that naturally occurring N2 fixing plankton assemblages in the NPSG are relatively resilient to large, short-term increases in pCO2. Keywords: Ocean acidification, Anthropogenic carbon, N-2 fixation, Nitrogen-fixation rates, Station Aloha, Marine microbes, Phosphorus limitation, Cyanobacterium Trichodesmium, Inorganic carbon